Asuhan Kebidanan Komprehensif Pada Ny. R Umur 24 Tahun G1P0A0 Dengan Kelainan Letak Janin Oblique Di Puskesmas Paguyangan Kabupaten Brebes - Laelatul Gorro; Endang Susilowati; Widi Astuti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
In Indonesia in 2020, there were 4,627 cases of MMR and 20,266 cases of IMR. One of the causes MMR and IMR is complications during pregnancy, childbirth, postpartum and newborn, even 47% of deaths of children under five occur during the neonatal period. Therefore, one of the efforts that can be made to prevent MMR and IMR is with comprehensive midwifery care that is carried out continuously. The purpose of this study was to be able to carry out Comprehensive Midwifery Care on Mrs. R aged 24 years. The research method used is descriptive qualitative method with a case study approach. The results of the research that has been done are known to Mrs. R experiencing oblique fetal position abnormalities in pregnancy 29 + 6 weeks. At delivery the fetus experienced fetal distress because Mrs. R experienced anxiety disorders so that delivery was performed by sectio caesarea, then at the neonate visit when the baby was 5 days old the baby experienced physiological jaundice, while in the postpartum period the mother did not experience any complications, then the mother chose MAL birth control. The conclusion of this study can be drawn that there is no gap between practice and theory.